Fraturas ósseas em mulheres na pós-menopausa: um estudo de coorte em Santa Maria/RS - Leal, Rafaela Martinez Copês (2021)
Osteoporosis is characterized by low bone mass associated with abnormalities in bone microarchitecture, increasing the risk of fragility fractures. Although there are guidelines for the diagnosis and treatment of osteoporosis, which could reduce the incidence of fractures by more than 70%, this disease continues to be underdiagnosed and undertreated. Knowledge of the epidemiology of fractures is essential for planning preventive actions and treatment strategies. Body mass index (IMC) is a major determinant of bone mineral density (BMD) and obesity is widely believed to protect against fracture. However, studies have challenged this assumption and have shown that fractures in obese people contribute substantially to the total number of fractures. Therefore, the aims of this study were to establish the incidence of bone fractures in the population of postmenopausal women attending the primary care in the municipality of Santa Maria, to evaluate their epidemiological characteristics, to access the FRAX algorithm utility is this population, and to evaluate the association between obesity and fractures. A cohort study was carried out in the municipality of Santa Maria, in women aged 55 years or older, in the post-menopause and who attended the basic health unit. The recruitment period was from March 1 to August 31, 2013. Participants were followed from September 1, 2013 until July 31, 2018. In the initial contact, a questionnaire was carried out and weight and height were measured. The follow-up was carried out on 854 women who contributed to 2732 people/year. It was done by annual telephone contact for 5 years. Information that included occurrence of bone fractures, diagnosis or treatment of osteoporosis, new comorbidities and use of medications was collected. In the fifth year of the study, visits were made to the basic heath unit to review the fracture incidence of the study participants. The average follow-up time was 3.2 years (SD 1.05; minimum follow-up 1.1 years and maximum 5.6 years). During this period, 62 fractures occurred in 58 women. The incidences of total fractures and major fractures in our study were 22.3 and 15.0 fractures per 1000 people/year, respectively. The most frequent fracture sites were 1) wrist, 2) shoulder, 3) ribs and, 4) hip. Hip fractures were the fourth most frequent site with an incidence of 3.3 fractures per 1000 people / year. Rheumatoid arthritis, previous fracture and use of glucocorticoids were risk factors for fractures in our study. Women who fractured had absolute 10-year fracture risk scores calculated by the higher FRAX algorithm than women who did not fracture. The incidence of fractures was similar among obese and non-obese women (24.2 per 1000 person/year vs. 22.9 per 1000 person/year, respectively; p=0.864 – Kaplan Meier). It is concluded that the incidence of fractures in postmenopausal women in Santa Maria was high and similar to other studies of Brazilian and Latin American populations and obesity is not a protective factor to bone fractures.